Investigation of luminescence signals of quartz and their application for provenance analysis and extending dating range of Brazilian fluvial sediments - Niyonzima, Pontien (2022)
This work investigates the feasibility of applying quartz radiofluorescence (RF) as provenance proxy, carried out experiments to evaluate if violet stimulated luminescence (VSL) of quartz is able to extend the dating age range of fluvial sediments in Brazil, and performed optically stimulated luminescence (OSL) dating to establish formation ages of ferruginous deposits (ironstones) of the Xingu River in Eastern Amazonia. The focus on luminescence properties of quartz from fluvial deposits is motivated by their widespread occurrence across Brazil, land of large rivers, thus, representing the most important continental record of landscape changes during the Quaternary. Firstly, the work examines RF emissions in quartz from parent rocks (igneous plutonic and volcanic) and sediments of different provenances. After deconvolution of RF spectra into its emission bands, emission band intensities were plotted versus OSL (first 1s) and 110°C thermoluminescence (TL) peak sensitivies to investigation whether RF emission band intensity can be used as sediment provenance. It has been shown that ultraviolet (UV) RF intensity correlates with both OSL and TL sensitivities of quartz from sediments. This correlation supported the suggestion that both 110°C TL peak and OSL of quartz use the same recombination centers rather than the same electron trap and that sensitization processes in nature of two signals might be due to the changes in recombination probability instead of changes in charge trapping probability. It is concluded that UV-RF intensity measured using X-ray sources can also be used for provenance analysis of sediments in the same way as the OSL and TL sensitivities. Characteristics of VSL signals of quartz from major fluvial systems from Western Brazil (Pantanal), Southeastern Brazil (Paraná River basin) and Central and Eastern Amazonia were investigated to assess if the VSL signal is suitable to extend the age range of luminescence dating of fluvial sediments. Single-aliquot regenerative dose (SAR), multiple aliquots regenerative dose (MAR) and multiple aliquots additive dose (MAAD) protocols were used to estimate the maximum dose that can be estimate by VSL signals for Brazilian sediments. Quartz VSL was found to significantly increase the dating limit to the Early Pleistocene (~800 ka to 1.6 Ma for the 2D0 MAAD) even with the relatively lower characteristic doses (D0) observed in dose response curves of the studied samples. Despite the improvement in luminescence age range of Brazilian fluvial sediments using VSL dating relative to the conventional OSL dating, the behavior of VSL appears to be sample dependent, with natural VSL signal missing in samples from Amazonian settings. In the estimation of formation ages of ironstones from the Xingu River, ages between ~60 ka and 3 ka were obtained using the SAR OSL dating protocol. This indicates that ironstones of the Xingu River result from a Late Pleistocene and Holocene surface geochemical system able to precipitate goethite and cement fluvial sediments under transport. The high dose rates (2.7-12.3 Gy ka-1) of these fluvial deposits limits the OSL dating to the last ~60 ka, assuming maximum doses of ~200 Gy estimated using quartz OSL applied to fluvial deposits across Brazil. The performed investigations improve the applicability of luminescence signals (RF, OSL and VSL) to obtain provenance and depositional age data from a variety of fluvial deposits occurring over Brazil. This is a contribution to expand the application of luminescence methods to study fluvial deposits.